2019
DOI: 10.15391/snsv.2019-3.007
|View full text |Cite
|
Sign up to set email alerts
|

Use of fitness trackers to determine the volume of physical activity of students in secondary schools aged 15–16 years

Abstract: Andriy Mandyuk. Use of fitness trackers to determine the volume of physical activity of students in secondary schools aged 15-16 years. Purpose: determine the weekly volume of motor activity of pupils of general education schools aged 15-16 in Lviv. Material & Methods: analysis of scientific and methodological literature, analysis and synthesis, determination of the volume of physical activity using technology FitnessTracker, methods of mathematical statistics. The study was attended by students of secondary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The distribution levels over the week are somewhat contradictory, with both less [ 20 ] and more [ 23 ] reported usage on Tuesdays and both higher [ 20 ] and lower [ 21 ] amounts of usage on weekends. Besides usage, more steps could be recorded on the weekend compared to weekdays [ 20 , 42 ]. Jeong et al reported high average wear times of about 8 h per day at weekends versus 11 h per day on Mondays and Tuesdays [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The distribution levels over the week are somewhat contradictory, with both less [ 20 ] and more [ 23 ] reported usage on Tuesdays and both higher [ 20 ] and lower [ 21 ] amounts of usage on weekends. Besides usage, more steps could be recorded on the weekend compared to weekdays [ 20 , 42 ]. Jeong et al reported high average wear times of about 8 h per day at weekends versus 11 h per day on Mondays and Tuesdays [ 21 ].…”
Section: Introductionmentioning
confidence: 99%